Development of a regional probabilistic seismic hazard model for Central Asia - V. Poggi; S. Parolai; S. Parolai; N. Silacheva; A. Ischuk; K. Abdrakhmatov; Z. Kobuliev; V. Ismailov; R. Ibragimov; J. Karaev; P. Ceresa; M. Santulin; et al. (Natural Hazards and Earth System Sciences)
Central Asia is an area characterized by complex tectonic and active deformation, largely due to the relative convergent motion between India–Arabia and Eurasia. The resulting compressional tectonic regime is responsible for the development of significant seismic activity, which, along with other natural hazards such as mass movements and river flooding, contributes to increased risk to local populations. Although several studies have been conducted on individual perils at the local and national levels, the last published regional model for the whole of Central Asia, developed under the EMCA (Earthquake Model Central Asia) project, is almost 10 years old.